2016
DOI: 10.1111/echo.13350
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of right ventricular dysfunction using transthoracic echocardiography in ARDS: a more objective approach

Abstract: Mild RV dysfunction is common after ARDS onset. RV morphologic changes coupled with dysfunction can be detected noninvasively through TTE changes with TAPSE, MPI, and FAC. Mild RV dysfunction by TAPSE is associated with ARDS severity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
3
19
1
Order By: Relevance
“…The reported incidence of RVD in ARDS varies across studies (22% to 50% (Table 1). [15][16][17][18][19][20][21][22][23][24] ) Although there is no robust evidence to support a definitive causal relationship between RVD and mortality in ARDS, it has been shown that RVD has a negative impact on the ARDS course and that severe RVD is associated with increased mortality even during lung protective mechanical ventilation.…”
Section: Epidemiology and Prognosismentioning
confidence: 99%
See 2 more Smart Citations
“…The reported incidence of RVD in ARDS varies across studies (22% to 50% (Table 1). [15][16][17][18][19][20][21][22][23][24] ) Although there is no robust evidence to support a definitive causal relationship between RVD and mortality in ARDS, it has been shown that RVD has a negative impact on the ARDS course and that severe RVD is associated with increased mortality even during lung protective mechanical ventilation.…”
Section: Epidemiology and Prognosismentioning
confidence: 99%
“…In a prospective observational study 20 which enrolled 226 patients with moderate to severe ARDS (Berlin definition) 25 (Table 1). 15,16 There is a need for a consensual definition that reflects the pathophysiology of RVD in the context of ARDS and positive pressure ventilation. This will enable intensive care specialists to identify patients at risk of RVF and implement strategies that may protect the RV.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…It’s reported that NT-proBNP is an important biomarker of heart failure [ 20 ]. Previous studies suggested that patients with diagnosis of ARDS often had right ventricular dysfunction [ 21 , 22 ], which would damage cardiopulmonary function. This study showed that, the levels of NT-proBNP on day 1 were increased in both groups, while the levels in control group were statistically significantly higher than those in the ARDS group ( p = 0.046).…”
Section: Discussionmentioning
confidence: 99%
“…At present, echocardiography is still the prefered choice for evaluating RV function of patients with ARDS, with the advantages of bedside, non-invasive and convenient. Tricuspid annular plane systolic excursion (TAPSE) is widely used as a quantitative index to evaluate RV function, which is highly correlated with the mortality of ARDS patients, thus providing a good parameter for us to interpret RV function in COVID-19 patients [9].…”
Section: Introductionmentioning
confidence: 99%